Current Practice of Neurosurgical Teleconsultation in Germany - Geiger, Matthias Florian; Wilhelmy, Saskia; Schmidt, Mathias; Firsching, Raimund; Groß, Dominik; Clusmann, Hans (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective As neurosurgery is a demanding specialty with services in larger medical centers only, consultation over larger distances plays an important role in health care. In times of digitalization, teleconsultation for medical images and cases plays an increasing role in neurosurgical services. However, no standards and demands have been established for its execution in the subfield of neurosurgery, so far. Therefore, as a first step, we performed a survey about the current state of teleconsultation in neurosurgery in Germany.Methods A standardized questionnaire consisting of 20 items was used to investigate the frequency of use and the operating conditions of teleconsultation in the field of neurosurgery. The survey was performed during the annual national German Society of Neurosurgery conference in 2017. Participation in the written survey was on voluntary and anonymous basis.Results In total, 296 individuals took part in the survey (140 specialists in neurosurgery, 77 residents). Among them, 71% were male and 121 worked at a university medical center. In total, 87.5% of all participants indicated that teleconsultation was used in their institutions (n = 113 in university medical centers and n = 76 in hospitals), and a vast majority stated to have had personal experience with it (88.6% of specialists, 85.5% of residents). The most frequent initial request for a consultation was done by phone call (80.3%). Images or data were then primarily transmitted via an electronic system (77.3%), followed by transmissions via CD or by post. The reply to a consultation was also mainly done by phone call (91.3%), followed by fax, or by e-mail. No standard protocol was followed by 78.6% of the respondents, and they stated not to know about the statutory and legal rules. However, it was stated that the protection of patient data was not endangered by using teleconsultation. The usefulness of teleconsultation and its future relevance were rated highly by the participants. The risk of misinterpretation of image data, especially without having direct access to other patient data, seemed to be a critical and unequivocal challenge.Conclusion The results of the survey demonstrate that teleconsultation for medical images and cases is a frequently used and well-accepted tool in neurosurgical health care. However, a standardized neurosurgical procedure is still lacking and the statutory rules for this field of digital medicine are generally not known in our community. Potential misinterpretation and resulting misjudgment seem to be realistic drawbacks. Thus, we see a necessity for elaboration of guidelines for teleconsultation in neurosurgery on national and European basis.
Keywords: telemedicine; teleconsultation; e-health; neurosurgery